RESPON PENGGUNA JALAN SEBELUM PELAKSANAAN PROYEK PENINGKATAN INFRASTRUKTUR JALAN DI KAWASAN GATOT SUBROTO KOTA SEMARANG - Hapsoro, Tunggul; Pratikso, Pratikso; Mudiyono, Rachmat (Pondasi, 2024)
The development of road infrastructure is a vital element in driving economic growth and improving the quality of urban life. In Semarang City, Jalan Gatot Subroto plays a crucial role as a major route connecting the north and south of the city, serving as a vital artery for inter-district mobility. However, in recent years, this road has faced serious challenges such as worsening traffic congestion, deteriorating road conditions, and their impacts on local social and economic activities. Therefore, efforts to enhance infrastructure on Jalan Gatot Subroto have become urgent given the complexity of these issues. This study aims to identify and determine variables that significantly influence the success of road improvement programs in the Gatot Subroto area of Semarang City. Data was collected using survey methods and deepened through interviews. The respondents involved in this study were 100 people with diverse backgrounds in terms of age and occupation. The collected data was then processed both quantitatively using SPSS and qualitatively to be used as a reference in answering research questions. Based on the analysis conducted, five variables are predicted to significantly affect the success of the road improvement project planned in the Gatot Subroto area of Semarang City: (1) User Satisfaction with a regression coefficient of 0.233, (2) Travel Time at 0.078, (3) Traffic Safety at 0.180, (4) Traffic Congestion at 0.163, (5) Accessibility at 0.551, and (6) Environmental Impact at 0.472. Referring to the field study results, it can be concluded that these variables have a significant relationship with the success rate of the Jalan Gatot Subroto improvement program in Semarang City, with important implications for more effective transportation infrastructure planning.